Genetic Variation of Duchenne Muscular Dystrophy and Cancer - Chen, Hubert (Medical Science: Trends and Innovations Vol. 11, 2025)
Duchenne muscular dystrophy (DMD) is a rare, severe, progressive genetic disorder causing disability and premature death. Mutations in the DMD gene encoding the dystrophin protein lead to the dystrophinopathies of DMD. Despite major therapeutic advances over the last few decades, there are currently no curative therapies for DMD. Gene therapy such as CRISPR-Cas9-based gene editing is a promising experimental approach to treat genetic diseases such as DMD. Interestingly, it has also been reported that muscular dystrophy patients may be at increased risk of malignancy. Although mutations in the DMD genes have been widely studied, a systematic genetic analysis of all variants, especially single nucleotide polymorphisms (SNPs), of the gene in humans has not been reported. In this study, a systematic analysis of the DMD genetic variants via the Single Nucleotide Polymorphism Database (dbSNP), and annotated the functions of the variants with wANNOVAR was performed. The protein-protein interaction (PPI) network for genetic modifiers identified in DMD patients was explored. DMD genetic alternations in different tumors have also been investigated via cBioPortal. Data mining and visualization were further performed based on the annotation. The study examined a total of 3,627 exonic SNPs in the DMD gene. SNPs are distributed across all exons. The largest category was nonsynonymous accounting for nearly 64% of all mutations. Exon 19 appeared to have the highest density of pathogenic SNP distribution. Nonsense mutation (i.e. stopgain) or frameshift mutation likely leads to more pathogenic. Among the genetic modifiers identified in DMD patients, THBS1 has higher network topological parameters, followed by SPP1, ACTN3 and LTBP4. Network analysis highlighted non-random interconnectivity between the genetic modifiers identified in DMD patients, and potentially shed light on new genetic modifiers by their functional coupling to these known genes. In conclusion, this is the first data mining study with a systematic genetic analysis of all variants, especially SNPs, of the DMD gene in humans. SNPs are distributed across all Exons. The largest category was nonsynonymous accounting for nearly 64% of all mutations. Exon 19 appeared to have the highest density of pathogenic SNP distribution. In addition, our results also suggest DMD gene may serve as a diagnostic and therapeutic target for certain types of cancer.